Ophthalmology breakthroughs in research and practice (Medical Information Science Reference (an imprint of IGI Global), 2018)
"This book is an innovative reference source for the latest academic material on the identification, treatment, and management methodologies of eye diseases and disorders. Highlighting a range of topics such as retinal prosthesis, ocular diseases, and ophthalmoscopy"--Provided by publisher